Digital Awareness and Competence Among Lecturers and Students for Enhancing French Language Instruction in Public Universities in South West, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
In this era of digital revolution the effective incorporation of technology into language teaching and learning has become essential, especially for foreign languages such as French teaching and learning. The study assessed lecturers' and students' digital awareness and competency in French Language teaching in public universities in South-West Nigeria. A descriptive survey research design was employed, and the target population consisted of all the lecturers and full-time undergraduate students studying French in public universities within the region. Using a multistage sampling technique, 63 lecturers and 892 students were sampled. Two structured questionnaires, namely the Lecturers' Preparedness for Digitalisation of Higher Education Instruction Questionnaire (LPDHEIQ) and the Students' Preparedness for Digitalisation of Higher Education Instruction Questionnaire (SPDHEIQ), were employed in collecting data. Each instrument included demographic information, digital awareness, and digital competency sections, on a four-point Likert scale. Expert review in educational technology and foreign language pedagogy validated it. Pilot testing in non-sample institutions provided high reliability coefficients (Cronbach's alpha = 0.79 for LPDHEIQ and 0.97 for SPDHEIQ). Online questionnaires were administered using Google Forms via email and social media. Descriptive statistics (means and standard deviations) addressed the research questions, and t-tests compared differences at the 0.05 level of significance. Findings revealed that lecturers had a moderate level of digital awareness and competence, whereas students had moderately high to high levels. There was a significant difference in digital competence in favor of the students. It is recommended that universities increase digital capacity-building and training activities that are explicitly designed to support French Language lecturers, to bridge the gap in digital competence and enhance instruction delivery.